differentiate arsinh(cosx))

let's start by defining y = arsinh(cos(x)). taking sinh of both sides gives sinhy = cosx. (since sinh(arsinhz) = z). Now we can differentiate both sides wrt x. The RHS differentiates to -sinx. We can use the chain rule for the LHS: d/dx = dy/dx *d/dy.so d/dx(sinhy) = dy/dx d/dy(sinhy) = dy/dx coshy. so dy/dx = -sinx/coshy. Now coshy = sqrt(1+(sinhy)^2) = sqrt(1+(cosx)^2).So dy/dx = -sinx/sqrt(1+(cosx)^2).

Related Further Mathematics A Level answers

All answers ▸

Solve (z-i)+(z+i)+(z-1)+(z-1)


Prove by mathematical induction that 11^n-6 is divisible by 5 for all natural numbers n


How do I construct a proof by induction?


Find the vector equation of the line of intersection of the planes 2x+y-z=4 and 3x+5y+2z=13.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences